Optical in-situ monitoring and correlation of density and mechanical properties of stainless steel parts produced by selective laser melting process based on varied energy density - Lu, Qing Yang (2020)
In-situ monitoring systems for additive manufacturing processes drive the possibility for identification of defects during printing, rendering both time and cost savings as the process can be stopped if a failure is detected. However, the relationship between defects identified during printing to the actual mechanical performance of the printed part has yet to be established. In this paper, we report the design and development of an optical based image processing in-situ monitoring system implemented on the selective laser melting process. The system consisted of an optical camera, a mirror and a set of light emitting diode lights. 316 L stainless steel specimens were fabricated with varying energy densities. Features captured in the optical images during printing were identified and quantified by image processing techniques. Results from density tests based on Archimedes’ principle and mechanical properties from tensile tests have demonstrated a correlation with the processed optical images of the specimens, validating the potential of inferring mechanical performance of printed parts based on features identified through the optical based image processing in-situ monitoring system.